An analysis of Human Resource practices of IPDC Finance Limited during COVID-19 and pre-COVID-19 period - Mahjabin, Syeda Nafisa (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.